Faktor-Faktor yang Berhubungan dengan Peranan Wanita dalam Agroindustri Ikan Asin di Kabupaten Tulang Bawang - Abdurrokhim, Muhammad; Rangga, Kordiyana K; Silviyanti S, Sherly (Suluh Pembangunan : Journal of Extension and Development, 2022)
The study aims to analyze the factors related to the role of women in the salted fish agroindustry. This study was conducted in Menggala Su-District and East Menggala Sub-District, Tulang Bawang District. Data retrieval on thes study was carried out in November-December 2020. This study used census analysis and the data were analyzed descriptively with a quantitative approach. The results showed that factors consisting of age, level of education, allocation of working hours, lenght of agroindustry business, and motivation are significantly related to the role of women in the salted fish agroindustry.